The route of hysterectomy: a comparative study between abdominal hysterectomy (AH), non descent vaginal hysterectomy (NDVH), and laparoscopic assisted vaginal hysterectomy (LAVH) - Uikey, Prashaant; Wankhede, Trupti M.; Tajne, Megha P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hysterectomy is the most common operation performed by the gynaecologist. The uterus can be removed using any of the technique and approaches, including abdominal, vaginal, laparoscopic. There are no formal guidelines available regarding the most appropriate route of hysterectomy. Hence, a comparison of the clinical results of the three routes of hysterectomy is needed. Methods: a prospective study was performed at Indira Gandhi government medical college Nagpur between September 2015- October 2017, among 150 women indicated to undergo hysterectomy for benign and mobile uterine conditions. They were assigned 50 each to three routes of hysterectomy (abdominal, non-descent vaginal hysterectomy and Laparoscopic assisted vaginal hysterectomy). Outcome measures including operating time, blood loss, fall in haemoglobin, intra-operative complications, duration of analgesia, VAS score, hospital stay and post-operative morbidity were assessed and compared between the three groups. Results: Fibroid uterus (65.33%), was the commonest indication for hysterectomy. As far as operating time, intra-operative blood loss, fall in haemoglobin, duration of analgesia, VAS score and hospital stay P Value was significant among the three group. Incidence of complications was least in the NDVH group. Conclusions: In developing country like India with poor health care resources, scarcity of beds and non-availability of sophisticated equipment NDVH offers a distinctive advantage over other route of hysterectomy and should be the route of choice for benign uterine conditions.